A novel multiplex qPCR targeting 23S rDNA for diagnosis of swine dysentery and porcine intestinal spirochaetosis. Issue 1 (December 2016) - Borgström, Anna; Scherrer, Simone; Kirchgässner, Constanze; Schmitt, Sarah; Frei, Daniel; Wittenbrink, Max
Abstract Background A multiplex qPCR targeting a 128 bp region on the 23S rDNA gene was developed for detection ofBrachyspira (B.) hyodysenteriae andB. pilosicoli, the agents of swine dysentery (SD) and porcine intestinal spirochaetosis (PIS), together with a triplet of apathogenicBrachyspira spp. (B. innocens, B. intermedia, B. murdochii ) in porcine feces. The multiplex qPCR was evaluated against a duplex PCR (La et al., J Clin Microbiol 41:3372–5, 2003). Results Using DNA extracted from fecal culture, the multiplex qPCR showed excellent agreement with the duplex PCR (κ = 0.943 and 0.933). In addition, thanks to the three probes whereof one detecting the apathogenicBrachyspria spp., a more diversified overview of the brachyspiral flora in porcine fecal samples can be delivered as a part of the routine diagnostic. The multiplex qPCR with a limit of detection of 5–10 genomic equivalents (GE) per reaction (6 × 102 GE per gram) allows reliable detection ofBrachyspira species directly from fecal swab DNA. In line with this, analysis of 202 fecal swabs in comparison with culture-based qPCR showed a high agreement for the causative agents of SD (B.hyodysenteriae: κ = 0.853, sensitivity 87% specificity 98%). Conclusion The novel multiplex qPCR is robust and has a high analytical sensitivity and is therefore suitable for high-throughput screening of porcine fecal swabs for the causative agents of SD. This assay can therefore be used for the direct proof of the pathogenicB . spp. in fecal swabs within the scope of a monitoring program.